Effects of protein sources and inclusion levels on nitrogen metabolism and urea kinetics of Nellore feedlot steers fed concentrate-based diets - Carneiro de Souza, Vinícius [UNESP]; Duarte Messana, Juliana [UNESP]; Darlisson Batista, Erick; Larissa Gomes Carvalho Alves, Kênia [UNESP]; Titgemeyer, Evan C.; Vaz Pires, Alexandre; Vinícius Ferraz Junior, Marcos; Galoro Silva, Lorrayny [UNESP]; Alberto Negrão, João; Eliodoro Costa, Vladimir [UNESP]; Generoso Ganga, Maria Júlia [UNESP]; Detogni Colovate, Paulo Henrique [UNESP]; et al. (Oxford University Press (OUP), 2021)
Urea recycling occurs in all mammalian species and represents an important source of ruminal nitrogen (N) for ruminants fed protein-restricted diets. However, its importance for cattle fed adequate amounts of protein and energy remains unclear. Six Nellore feedlot steers fed concentrate-based diets were used in a 6 × 6 Latin square design with a 3 × 2 factorial arrangement of treatments to evaluate ruminal fermentation, urea kinetics, and N excretion. Treatments consisted of 3 protein sources (PS: soybean meal plus urea [SU], corn gluten meal [CGM], and dry distillers grains [DDG]) and 2 inclusion levels (PL; 11% and 14%). Steers were adapted to the diets for 14 d followed by 8 d of sample collection. Feed intake, fecal output, and urine production were measured from day 18 to day 22 of each period. Blood samples were collected every 6 h on day 18. [15N-15N]-urea was infused into the jugular vein for 82 h over day 19 to day 22, and measurement of 15N in background (day 18) and enriched feces and urine (day 21) were used to evaluate urea kinetics. To evaluate the incorporation of recycled urea N into microbial protein (MICP), ruminal and duodenal fluid were collected on day 22. Steers fed SU diets had lower (P < 0.05) nitrogen use efficiency (NUE), greater (P < 0.05) urea-N entry rate (UER), and tended (P < 0.10) to have greater gastrointestinal entry rate of urea-N (GER) compared with those fed CGM or DDG. In addition, steers fed SU had greater (P < 0.05) urea-N returned to ornithine cycle (ROC) compared with those fed CGM or DDG. Increasing PL tended (P < 0.10) to increase UER. The proportion of total microbial N from recycled urea-N was greater (P < 0.05) for steers fed CGM compared with those fed SU and also greater for steers fed diets with 11% CP than for those fed with 14% CP. Diets with 11% CP can be used for Nellore feedlot cattle fed concentrate-based diets without negatively affecting intake, digestibility, and ruminal fermentation. Moreover, diets containing rumen undegradable protein (RUP) feed sources (CGM or DDG) compared with diets with SU markedly increased NUE, while maintaining microbial protein (MICP) synthesis. Results from this study suggest that the equation adopted by NASEM (NASEM. 2016. Nutrient requirements of beef cattle. 8th revised ed. Washington, DC: The National Academies Press) was not accurate in estimating the urea-N used for anabolism (UUA) in Nellore feedlot cattle fed concentrate-based diets.
Keywords: anabolism; cattle; excretion; urea recycling